KINESITHERAPEUTIC APPROACH FOLLOWING SURGICAL TREATMENT IN CASES OF PARTIAL OR COMPLETE MUSCLES' RUPTURE OF THE ROTATOR CUFF - Gergana Nenova (Peytchinski Publishing, 2019)
Problems in the shoulder area are frequently encountered and result in significant limitations in the volume of movement, pain and inability to perform daily activities. Material and methods: For a period of 18 months, 12 patients with rotator cuff tears have passed through the kinesitherapy office at the Department of Orthopaedics and Traumatology at St. Marina Marina University of Varna. Every one of these patients underwent surgical treatment and extensive kinesitherapy until about the 6th month after the operation. 7 of the patients are male, and 5 are female with the average age being 48 years for the men and 55.4 for the women. Results: Satisfactory results were achieved in regards to the volume of joint movement in 10 of the patients as a result of the surgical treatment performed in the 12 cases (recovery of the rotator cuff with the help of shoulder fixation anchors attached to the affected tendons) and the extensive kinesitherapeutic treatment. Conclusion: Applying the kinesitherapeutic treatment that is presented in the report, in the cases of patients with shoulder pathology, determines their complete functional recovery and improvement to the quality of life.